2015
DOI: 10.5455/2320-6012.ijrms20150510
|View full text |Cite
|
Sign up to set email alerts
|

Foeto-placental weight relationship in normal pregnancy and pregnancies complicated by pregnancy induced hypertension and abruption of placentae

Abstract: Background: The aim of this study was to study the effects of pregnancy induced hypertension and abruption of placenta on foeto-placental weight ratio and its comparison with normal group. Methods: In this comparative study hundred and twenty placentae were collected from labor room and gynecology operation theatre of Liaquat University hospital. Forty placentae from parturient that had pregnancy induced hypertension & forty placentae from parturient with history of Abruption of placenta & forty cases belonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
3
4
0
Order By: Relevance
“…Mehare et al and Goswami et al also reported decrease in FTP ratio in hypertensive groups compared to the normal placentae. 16,17 These findings are consistent with those observed in our study. This decline in FTP may be due to placental insufficiency associated with altered dimension of placental tissue, neonatal morbidity and ultimately with preterm deliveries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mehare et al and Goswami et al also reported decrease in FTP ratio in hypertensive groups compared to the normal placentae. 16,17 These findings are consistent with those observed in our study. This decline in FTP may be due to placental insufficiency associated with altered dimension of placental tissue, neonatal morbidity and ultimately with preterm deliveries.…”
Section: Discussionsupporting
confidence: 93%
“…13,15 A study by Goswami et al reported pregnancyinduced hypertension as an independent risk factor for causing low birth weight. 16 The mean fetoplacental weight ratio was decreased in the placentae of hypertensive group compared with their normal counterparts in the present study. Mehare et al and Goswami et al also reported decrease in FTP ratio in hypertensive groups compared to the normal placentae.…”
Section: Discussionsupporting
confidence: 42%
“…Palaskar observed mean fetoplacental ratio in normal pregnancy was 5.8 and 7 : 1, and in PIH, the mean fetoplacental ratio was increased to 6.04. While Gunapriya in 2011 observed the fetoplacental ratio of 5.35 in normal and in PIH, 6.03 [19], Ananth observed in abruption of placenta mean birth weight and placental weight were lower especially in preterm births with placental ratio <10 th centile risk ratio 0.4, 95% CI 0.2-0.8 [20]. Several studies show reduced placental weight in abruption also a low birth weight of newborn, but the fetoplacental ratio was not calculated which was significant in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Navbir P found 2.16, 2.59 and 2.79 kg mean foetal weight in eclampsia, moderate and mild preeclampsia respectively [13]. Goswami P et al stated that during pregnancy, the placental mass maintains a dynamic relationship with the weight of developing foetus [8]. Shah RK commented that weight of placenta and birth weight are more decreased in preeclampsia with oedema than that without oedema but in severe preeclampsia both will be decreased probably due to marked proteinuria [18].…”
Section: Observations and Resultsmentioning
confidence: 99%